2015
DOI: 10.3892/ijmm.2015.2161
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Dpysl2 expression are associated with prenatally stressed rat offspring and susceptibility to schizophrenia in humans

Abstract: Exposure to stress during critical periods of fetal brain development is an environmental risk factor for the development of schizophrenia in adult offspring. In the present study, a repeated-variable stress paradigm was applied to pregnant rats during the last week of gestation, which is analogous to the second trimester of brain development in humans. Behavioral and proteomic analyses were conducted in prenatally-stressed (PNS) adult offspring and non-stressed (NS) adult controls. In the behavioral tests, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…Interestingly, the Trx1:Crmp2 interaction was mapped to the Cys504 residue of Crmp2, suggesting that Trx1 is an important determinant of Crmp2 posttranslational modifications and function [46]. Although Crmp2 has been primarily associated with neurological diseases including Alzheimer’s and schizophrenia [4750], Crmp2 is highly expressed in lung tissue as well as lung tumor cells [51]. Although endogenous function of Crmp2 in the lung remains unknown, differential Crmp2 posttranslational modifications are associated with nonsmall cell lung cancer [52].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the Trx1:Crmp2 interaction was mapped to the Cys504 residue of Crmp2, suggesting that Trx1 is an important determinant of Crmp2 posttranslational modifications and function [46]. Although Crmp2 has been primarily associated with neurological diseases including Alzheimer’s and schizophrenia [4750], Crmp2 is highly expressed in lung tissue as well as lung tumor cells [51]. Although endogenous function of Crmp2 in the lung remains unknown, differential Crmp2 posttranslational modifications are associated with nonsmall cell lung cancer [52].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the expression of neurofilament and Dpysl2 proteins in the offspring of rats with PNS was affected by VF treatment. Our previous studies have shown that Dpysl2 and neurofilament protein levels decreased in the offspring of rats exposed to PNS (36,37). Furthermore, according to our unpublished data, Lasp1 protein was also downregulated in the PNS group.…”
Section: Discussionmentioning
confidence: 50%
“…All experimental procedures were reviewed and approved by the institutional Review Board for Animal Welfare at Soonchunhyang University. The rat model of PNS was established as described in our previous studies (36,37). Briefly, PNS exposure was initiated on day 14 of gestation and continued until day 21, and consisted of: i) 1 h restraint in a well-ventilated, cylindrical Plexiglas restraint device (Braintree Scientific, Inc. Braintree, MA, USA), ii) 6 h of exposure to a cold environment (4˚C), iii) overnight fasting, iv) 15 min of swimming stress in room-temperature water, v) reversal of the light-dark cycle, and/or vi) social stress induced by overcrowded housing conditions during the dark phase (28,29).…”
Section: Prenatal Stress Procedures Prenatal Stress Proceduresmentioning
confidence: 99%
“…Dpysl2, multifunctional protein of the nervous system, plays a role in neuronal development and polarity, as well as in neuron projection morphogenesis, necessary for signaling-related remodeling of the cytoskeleton (26). Dpysl2 is related to schizophrenia disorder (27). Over-expression of the Dpysl2 causes an increase in the Ca2+ channel density, and CaV2.2 channels have shown a significant increase in vesicular release due to a depolarizing stimulation.…”
Section: Discussionmentioning
confidence: 99%